Determinant Factors of Income of Cocoa Farmers in Batuparigi Village, Mamuju Tengah District - Arwin Sanjaya; Nur Astaman Putra; Salmi Taedy (Jurnal Ad'ministrare, 2021)
Cocoa farming is a business developed by the community in Batuparigi Village, Tobadak District, Central Mamuju Regency so that cocoa is one of the leading agricultural sectors there. However, there are several inhibiting factors, such as; The increasing price of cocoa seedlings has made it difficult to obtain quality seeds. In addition, the cost of fertilizers and pesticides has increased in price from year to year and has become an obstacle for cocoa farmers. This study uses a quantitative approach with a survey method. The sample in the study was 30 people. The data collection techniques used were observation, documentation, and questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously the independent variables (land area, fertilizer costs, seed costs, pesticide costs, and labor) had a significant and positive effect on the dependent variable (farmer income). Partially, land area has a significant effect and is positively related, while the variable cost of fertilizer, cost of seeds, cost of pesticides, and labor has no significant effect on farmers' income